Gröna broar : ekologiska, sociala och estetiska tillgångar - Blomfeldt, Jonna (SLU/Dept. of Urban and Rural Development, 2013)
The visions of the United Nations concerning sustainable development and conservation of biodiversity can only be realized if the human population succeeds in creating coexistence between human and wildlife. Landscape architects are able to influence on how landscapes are to be maintained and developed. The negative impact of infrastructure on wildlife has become a critical problem in Sweden and other parts of Europe. Wildlife crossings has been developed as a solution for the problems of road barriers in the landscape. The crossings are made to give animals a better opportunity to cross roads. There are a lot of different models of crossings, for different needs. The overbridging crossings are called wildlife bridges or green bridges. In the Netherlands the problems of barriers have become so critical that they have had parts of the road network demolished. In Sweden it is not yet too late to include green bridges and other wildlife crossings in planning processes and spare the need of demolishing existing roads. The main reason why green bridges have not been used as a method in Sweden is because of high economic costs, small quantity of traffic and because of a different design culture. Ian Thompson has created a model for good landscape architecture which has been used in this essay. The model is called trivalent design and embraces three equal values: ecology, aesthetics and social awareness. Trivalent design also here represents the relationship and contribution of landscape architecture to sustainable development. Can green bridges become ecological, aesthetic and social assets in urban areas? Do they have the potential to be good and sustainable landscape architecture? The result was obtained by reading information about green bridges, Thompsons book Ecology, Community and Delight and literature on urban planning. Several benefits of the use of green bridges in Sweden urban areas in the future were found. One ecological benefit was that planning for green bridges are a relatively simple positive step to take for landscape architects and planners in the conflict between human life habits and nature. Aesthetic benefits from green bridges were that they can strengthen a community identity. Green bridges can also serve as reference points in the local environment and help people to orientate in the cities. Thanks to better accessibility to green spaces a lot of social benefits could be noticed, such as: increased physical and mental health, decreased segregation and greater ecological awareness. Ecological infrastructure is a topic that would gain on being exhibited as a topic with prospects in a lot of different values. Green bridges could be examples of great landscape architecture in Sweden.